2021
DOI: 10.3390/s21206790
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leg Push Forces and Their Relationship to Velocity in On-Water Sprint Kayaking

Abstract: The purpose of this work was to describe the leg-muscle-generated push force characteristics in sprint kayak paddlers for females and males on water. Additionally, the relationship between leg pushing force characteristics and velocity was investigated. Twenty-eight paddlers participated in the study. The participants had five minutes of self-chosen warm-up and were asked to paddle at three different velocities, including maximal effort. Left- and right-side leg extension force were collected together with vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…If a longer compression force duration would be associated with a greater range of motion of the knee, results are in line with a previous study [3], that suggested that greater knee amplitude are associated with elite kayakers' performance. Nilsson and colleagues [1] observed that kayak speed decreased by 16% with the restriction of movement of the lower limbs and also reported a high correlation between pushing forces and kayak velocity, which suggests that the force applied by the lower limbs considerably influences the kayaking performance [6]. Previously, Begon and colleagues [5], based on computer modeling to access the lower limb contribution to kayak performance, suggested that the legs produce 6% of the total propulsion on a sliding kayak ergometer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If a longer compression force duration would be associated with a greater range of motion of the knee, results are in line with a previous study [3], that suggested that greater knee amplitude are associated with elite kayakers' performance. Nilsson and colleagues [1] observed that kayak speed decreased by 16% with the restriction of movement of the lower limbs and also reported a high correlation between pushing forces and kayak velocity, which suggests that the force applied by the lower limbs considerably influences the kayaking performance [6]. Previously, Begon and colleagues [5], based on computer modeling to access the lower limb contribution to kayak performance, suggested that the legs produce 6% of the total propulsion on a sliding kayak ergometer.…”
Section: Discussionmentioning
confidence: 99%
“…These results were confirmed in an on-water kayaking study, also comparing restricted and unrestricted, and concluded that the restriction of lower limbs leads to a significant reduction of the kayak velocity (−16%) and a decrease of the bilateral mean stroke force (−21%), however, in terms of the time pattern of the occurrence of the peak force on the foot rest and foot strap, there were no significant changes [1]. Futhermore, the impulse of the push forces on the foot rest over 10 s showed the highest correlation to maximum kayak velocity [6].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, one should be cautious not to interpret these findings as increasing stroke length through a delayed exit of the blade from the water that would impair boat speed and consequently increase drag force (Gomes et al 2015). Instead, international elite athletes of better performance level distinguishes from national level athletes by a greater range of motion in knee extension, increasing pelvis and trunk rotation which ultimately increased stroke length through a well forward catching phase (Limonta et al 2010; Klitgaard et al 2021). However, they maintain the exit phase once the blade reaches the vertical position to quickly initiate the contralateral catching phase while reducing ineffective portion of the stroke (Gomes et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Leg contribution in flatwater kayaking should also not be discarded. Providing the feet are strapped on the footrest, the kayakers performed push and pull actions with their legs to enhance pelvis and trunk rotation (Nilsson et Rosdahl 2016; Limonta et al 2010; Klitgaard et al 2021) (Nilsson et Rosdahl 2016) estimated to 0.2 seconds the duration of the synchronized period between leg extension and paddle thrust. Although of short duration, synchronization between leg extension, pelvis, and trunk rotation, as well as paddle thrust, needs to be finely refined to provide gain in boat velocity quantified from 6% (Begon, Colloud, et Sardain 2010, 201) to 16% (Nilsson et Rosdahl 2016).…”
Section: Introductionmentioning
confidence: 99%